Perception of Nursing Students Regarding Clinical Learning Environment, Supervision (CLES) - Poonam Sheoran; Simarjeet Kaur; Neha Patyal; Neetu; Hemlata; Jyoti Sarin (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: In nursing education, clinical placement is a vital part of nursing students’ education. Theclinical learning environment is considered as first place of professional practice for nurses and student’sopinion contributes to its improvement. Theaim of the current study was to assess the perception of nursingstudents regarding clinical learning environment supervision in obstetric and gynecological department.Method: A quantitative research approach with descriptive survey research design was used to collect datafrom 222 nursing students using total enumerative sampling technique from September 2017 to April 2018.Clinical Learning Environment and supervision scale (CLES) was used to assess the perception of nursingstudents with their clinical learning environments. Results: The study results showed that the sub domainof supervisory relationship (90.62%) was having highest mean percentage and relationship between student,staff and teacher sub domain has lowest mean percentage (84.38%). The nursing students evaluated the subdomain of relationship between student, staff and teacher (22.07%) as ‘need to improve’ andintegrationof theory and practice (67.57%) as ‘good.’There is significant positive co-relation between all domains ofclinical learning and supervision.Conclusion: It was found that the student valued supervision, pedagogical and learning environment.Majority of nursing students experienced the content of supervisory relationship was the most importantdimension in CLES. This means that nursing students were oriented tounit settings/ wards by clinicalinstructor/teacher, they felt that they receive individualized supervision and continuous feedback andsuggestions of improvement from clinical instructors/teacher and there were frequent bed side rounds.